2021
DOI: 10.1101/2021.09.17.460759
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perception affects the brain’s metabolic response to sensory stimulation

Abstract: Processing of incoming sensory stimulation triggers an increase of cerebral perfusion and blood oxygenation (neurovascular response) as well as an alteration of the metabolic neurochemical profile (neurometabolic response). Here we show that perceived and unperceived isoluminant chromatic flickering stimuli designed to have similar neurovascular responses as measured by blood oxygenation level dependent functional MRI (BOLD-fMRI) in primary visual cortex (V1) have markedly different neurometabolic responses as… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 99 publications
(141 reference statements)
0
4
0
Order By: Relevance
“…The cerebral metabolic rate of oxygen can be used to measure oxidative phosphorylation of ATP, and a nonoxidative component, aerobic glycolysis, is reflected by lactate accumulation (Fox et al, 1988). DiNuzzo et al reported that stimulus perception affects the lactate and glutamate response in the primary visual cortex in a 3T-fMRS study (DiNuzzo et al, 2022). Further, an fMRS study suggesting habituation of neuronal firing showed that the BOLD response was preserved while the lactate accumulation was reduced over time during repeated photic stimulation (Mangia, Tkac, Logothetis, et al, 2007).…”
Section: Mrs Spectra Fitting For Glutamate-glutamine Complex and Lactatementioning
confidence: 99%
See 3 more Smart Citations
“…The cerebral metabolic rate of oxygen can be used to measure oxidative phosphorylation of ATP, and a nonoxidative component, aerobic glycolysis, is reflected by lactate accumulation (Fox et al, 1988). DiNuzzo et al reported that stimulus perception affects the lactate and glutamate response in the primary visual cortex in a 3T-fMRS study (DiNuzzo et al, 2022). Further, an fMRS study suggesting habituation of neuronal firing showed that the BOLD response was preserved while the lactate accumulation was reduced over time during repeated photic stimulation (Mangia, Tkac, Logothetis, et al, 2007).…”
Section: Mrs Spectra Fitting For Glutamate-glutamine Complex and Lactatementioning
confidence: 99%
“…Further, an fMRS study suggesting habituation of neuronal firing showed that the BOLD response was preserved while the lactate accumulation was reduced over time during repeated photic stimulation (Mangia, Tkac, Logothetis, et al, 2007). For lactate analysis, we screened participants with CRLB of lactate < 35% (DiNuzzo et al, 2022).…”
Section: Mrs Spectra Fitting For Glutamate-glutamine Complex and Lactatementioning
confidence: 99%
See 2 more Smart Citations